She speaks!: what Shakespeare's women might have said - Walter, Harriet (Virago Press, 2024)
"Dame Harriet Walter is one of Britain's most esteemed Shakespearean actors. Now, having played most of the Bard's female characters, audaciously she lets them speak their minds. With thirty new parts for Shakespeare's women, written in 'Shakespearean' verse and prose, Harriet Walter goes between the lines of the plays to let us hear what she imagines - sometimes playfully and sometimes searchingly - these women were really thinking."--Publisher